Learning game for training child bicyclists' situation awareness. (August 2017) - Lehtonen, Esko; Sahlberg, Heidi; Rovamo, Emilia; Summala, Heikki
Highlights: A learning game was developed to improve children's situation awareness in bicycling. The effect of the game was tested with 8–9 year olds with SAGAT like tests. Signal Detection Theory was used to analyze the results. The game did not improve sensitivity in the tests, but it decreased answer latency. Abstract: Encouraging more children to bicycle would produce both environmental and health benefits, but bicycling accidents are a major source of injuries and fatalities among children. One reason for this may be children's less developed hazard perception skills. We assume that children's situation awareness could be trained with a computer based learning game, which should also improve their hazard perception skills. In this paper, we present a prototype for such a game and pilot it with 8–9 year old children. The game consisted of videos filmed from a bicyclist's perspective. Using a touchscreen, the player's task was to point out targets early enough to gain points. The targets were either overt (other visible road users on a potentially conflicting course) or covert (occlusions, i.e. locations where other road users could suddenly emerge). If a target was missed or identified too late, the video was paused and feedback was given. The game was tested with 49 children from the 2nd grade of primary school (aged 8–9). 31 young adults (aged 22–34) played the game for comparison. The effect of the game on situation awareness was assessed with situation awareness tests in a crossover design. Similar videos were used in the tests as in the game, but instead of pointing out the targets while watching, the video was suddenly masked and participants were asked to locate all targets which had been present just before the masking, choosing among several possible locations. Their performance was analyzed using Signal Detection Theory and answer latencies. The game decreased answer latency and marginally changed response bias in a less conservative direction for both children and adults, but it did not significantly increase sensitivity for targets. Adults performed better in the tests and in the game, and it was possible to satisfactorily predict group membership based on the scores. Children found it especially difficult to find covert targets. Overall, the described version of the learning game cannot be regarded as an effective tool for situation awareness/hazard perception training, but ways to improve the game are discussed.